Antecedentes à resistência à implantação de sistemas de informação: uma análise de sistemas de gestão eletrônica de documentos - Muniz, Allan de Souza (2012)
The following work seeks the development of metamodel for the study of the resistance phenomenon during implementation of an Electronic Document Management System. The study was conducted by an explanatory, quantitative approach and identified the main academic authors of resistance. Based on their assumptions, the most relevant factors regarding resistance applied to Electronic Document Managament Systems were shown. The created metamodel, which was used for statistical analysis, identified the following predecessors to resistance behavior: individual characteristics, systems and interaction. This last vector is divided itself into two subsystems: power and politics interaction and socio-technical interaction. As from the identification of these vectors and construction of the proposed model, a survey has been applied on the Internet. 133 responses from users who had been through with a least one Electronic Document Management implementation were obtained. The data were then submitted to statistical analysis in SPSS software through factorial analysis and multiple linear regression. The results allowed the identification of the main factors responsible for resistance behavior and confirmed/refused the original proposed hypotheses. The final metamodel also allowed the elaboration of a discussion of the results based on theory, bringing new insights for the understanding of resistance behavior within the EDM context.